MTHFR C677T rs1801133 GENE POLYMORPHISM AS A RISK FACTOR FOR NONSYNDROMIC CLEFT PALATE ONLY AMONG DEUTERO MALAY SUB RACE IN INDONESIA (POLIMORFISME GEN MTHFR C677T rs1801133 SEBAGAI FAKTOR RISIKO CELAH LANGIT-LANGIT NON SINDROMIK SUBRAS DEUTERO MELAYU IND - Saskia L. Nasroen; Tichvy Tammama; Gracia AN Putri (Journal of Health and Dental Sciences, 2022)
Nonsyndromic cleft palate only (NS CPO) is a congenital malformation that arises from palatal fusion failure process at the seventh week of palatogenesis with a prevalence of 1:1000 live birth worldwide. The MTHFR C677T rs1801133 gene polymorphism is one candidate gene that can be associated with NS CPO. This study aims to determine the risk factor for NS CPO through MTHFR C677T rs1801133 analysis among the Deutero Malay subrace of the Indonesian population. This study was a case-control design, using samples from venous blood of 50 NS CPO subjects and 51 healthy control subjects. After DNA was extracted, followed by PCR, the PCR-RFLPs method was performed using the HinfI restriction enzyme. The Chi-Square test was used with the Kolmogorov Smirnov and Exact Fisher alternatives. The results showed that CT genotype (OR=2,960, p<0.05) of MTHFR C677T rs1801133 gene polymorphism can increase the risk of NS CPO. MTHFR C677T rs1801133 gene polymorphism is a risk factor associated with NS CPO among the Deutero Malay subrace in the Indonesian population. DOI : 10.54052/jhds.sd22.p195-208